Clinical and molecular study of radiation-induced gliomas - Trkova, Katerina; Sumerauer, David; Bubenikova, Adela; Krskova, Lenka; Vicha, Ales; Koblizek, Miroslav; Zamecnik, Josef; Jurasek, Bruno; Kyncl, Martin; Malinova, Bela; Ondrova, Barbora; Jones, David T. W.; et al. (Scientific reports, 2024)
In this study, we provide a comprehensive clinical and molecular biological characterization of radiation-induced gliomas (RIG), including a risk assessment for developing gliomas. A cohort of 12 patients who developed RIG 9.5 years (3-31 years) after previous cranial radiotherapy for brain tumors or T-cell acute lymphoblastic leukemia was established. The derived risk of RIG development based on our consecutive cohort of 371 irradiated patients was 1.6% at 10 years and 3.02% at 15 years. Patients with RIG glioma had a dismal prognosis with a median survival of 7.3 months. We described radiology features that might indicate the suspicion of RIG rather than the primary tumor recurrence. Typical molecular features identified by molecular biology examination included the absence of Histon3 mutation, methylation profile of pedHGG-RTK1 and the presence of recurrent PDGFRA amplification and CDKN2A/B deletion. Of the two long-term surviving patients, one had gliomatosis cerebri, and the other had pleomorphic xanthoastrocytoma with BRAF V600E mutation. In summary, our experience highlights the need for tissue diagnostics to allow detailed molecular biological characterization of the tumor, differentiation of the secondary tumor from the recurrence of the primary disease and potentially finding a therapeutic target.